Viuvez e reprodução assistida "Post-Mortem": um processo de luto e de decisão - Moreira, Marta Nascimento (2012)
Post-Mortem Assisted Reproduction is a subject that belongs to the contemporary world, brought to reality with the biotechnology development and reproduction medicine field progress, which made possible the conception after an individual s death. This subject brings many ethic, political, religious and economic issues that are discussed worldwid, including questions about parenthood, family, life and death. This qualitative research aimed at understanding the meanings given by a widow to her decision about what to do with the deceased husband s cryopreserved genetic material and also to analyze the relation between this decision and the bereavement process. This discussion includes two human relationship domains: the making and the breaking of an affective bond. Therefore, Attachment Theory and the Dual Process Model of Grief were used as background of this research, giving support to its analysis. A widow has willingly accepted to contribute for this study. By means of a semi-structured interview, it was possible to understand her relation with the deceased, the context in which the sperm was collected, the husband s death story and the widow s decision on what to do with the semen. Three important experiences affected her decision: her husband s struggle against cancer; after the husband s death; living a new loving relationship. The widow s decision was taken along with the bereavement process, during her husband s illness and death, and were understood as indicators of the bereavement process. Meanings attached to her bereavement process were identified, such as a possibility even with the partner s death, the product of a built loving relation and failure in accomplish the parental project